Systemic lupus erythematosus in a 9-year-old patient with beta-thalassemia trait. A case report - Ninik Sukartini Ninik Sukartini (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
We reported a case of lupus nephritis in a 9-year-old patient with beta-thalassemia trait who was treated in Cipto Mangunkusumo Hospital. The patient presented with bicytopenia, hepatosplenomegaly and lymphadenopathy. Laboratory results revealed hematologic disorder, i.e. hemolytic anemia with positive Coombs' test and thrombocytopenia, positive ANA and antibody to double-stranded DNA, and proteinuria of 1230 mg/24 hrs, which fulfilled 4 criteria of ACR for the diagnosis of systemic lupus erythematosus ISLE). Signs of pericarditis was not found. In the follow up, the patient showed microcytic hypochromic anemia with high transferrin saturation level, leading to hemoglobin analysis which revealed beta thalassemia trait. This case is interesting because this patient didn't present with characteristic clinical features, and because SLE is seldom diagnosed before 16 years of age. Moreover, this patient also suffered from beta thalassemia trait, which is known to be associated with rheumatoid arthritis, another autoimmune disorder.Key words: SLE, lupus nephritis, beta thalassemia trait, childhood age